Il Tagikistan sovietico negli scritti di Bruno Jasieński e Ryszard Kapuściński .......... 141 - Gurgul, Monika (Pensées orientale et occidentale : influences et complémentarité II, 2021)
SOVIET TAJIKISTAN IN THE WORKS OF BRUNO JASIEŃSKI AND RYSZARD KAPUŚCIŃSKIThe political situation in Central Asia involved in the development of European imperialism in the XIX-XX centuries, was reflected by different Polish authors. The article is dedicated to the image of Tajikistan created by Bruno Jasieński and Ryszard Kapuściński in different moments of Soviet domination: the time when the new regime was born, the period of its decline in the ’60s, and during perestroika.